The Effect Giving Banana (Musa Paradisiaca Normalis) Blossoms On Smooth Breastfeeding For Post-Partum Mothers At Cahaya Clinic, Lubuk Pakam Regency In 2024 - Saragih, Astri Ulina; Sunengsih; Yulanda, Risky; Prisilya, Popy; Sinaga, Andini (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Introduction: Banana blossom s a type of plant that contains lactagogum which has the potential to stimulate the hormones oxytocin and prolactin such as alkaloids, polyphenols, steroids, flavonoids and other substances which are most effective n ncreasing and facilitating production. Objective: To determine the smooth daily volume of breast milk n post partum mothers before giving banana blossoms and to determine the smooth daily volume of breast milk n post partum mothers after giving banana blossoms. Method: This research uses a quantitative research design with a one group pretest-posttest design model, that s, before t s carried out, observations are made on the sample and after treatment, observations are made again. The data collection technique was carried out using an ncidental sampling technique. Results: Based on the probability of the test results listed n the table, t can be seen that the resulting probability s 0.000. This means that the probability < level of significance (? = 0.05), so that Ha s accepted and H0 s rejected. Thus, t can be stated that there s a significant difference between the smoothness of post-partum mothers’ breast milk before giving banana blossoms (Pretest) and the smoothness of post-partum mothers’ breast milk after giving banana blossoms (Posttest). Conclusion: So t can be said that there s an nfluence of giving banana (Musa Paradisiaca Normalis) blossoms on Smooth breastfeeding for post-partum mothers at Cahaya Clinic, Lubuk Pakam Regency in 2024.